1999
DOI: 10.1126/science.284.5411.167
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Area 17 in Visual Imagery: Convergent Evidence from PET and rTMS

Abstract: Visual imagery is used in a wide range of mental activities, ranging from memory to reasoning, and also plays a role in perception proper. The contribution of early visual cortex, specifically Area 17, to visual mental imagery was examined by the use of two convergent techniques. In one, subjects closed their eyes during positron emission tomography (PET) while they visualized and compared properties (for example, relative length) of sets of stripes. The results showed that when people perform this task, Area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
347
5
10

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 640 publications
(399 citation statements)
references
References 21 publications
27
347
5
10
Order By: Relevance
“…For example, one can use the model to synthesize novel "scenes". In the context of cortical networks, this is consistent with the ideas that early visual cortical areas are involved in generating visual mental imagery [27,28]. The ability to use the framework to infer, discriminate, synthesize, compress etc.…”
Section: Resultssupporting
confidence: 83%
“…For example, one can use the model to synthesize novel "scenes". In the context of cortical networks, this is consistent with the ideas that early visual cortical areas are involved in generating visual mental imagery [27,28]. The ability to use the framework to infer, discriminate, synthesize, compress etc.…”
Section: Resultssupporting
confidence: 83%
“…The reduction in activity in BAs 17, 18 and 19 during Zazen suggests reduced visual imagery (Kosslyn et al 1993(Kosslyn et al , 1999. This is especially noteworthy since our practitioners had their eyes only two-thirds closed during Zazen compared to having them completely closed during resting.…”
Section: Discussionmentioning
confidence: 79%
“…Controversy persists about such activation of the primary visual area during visual mental imagery. Some studies [13,24,25] have reported activation during tasks requiring visual mental imagery of objects, while others [28] have not found such evidence. However, a recent study [29] has highlighted the influence of learning modality upon these effects, with visually learnt images producing less activation in the early visual cortex than images produced by verbal description, as in the present investigation.…”
Section: Creative -Uncreative Contrastsmentioning
confidence: 99%